Die Begräbnisfeierlichkeiten nach dem Tod Ferdinands I. und seiner Söhne / Funeral rites after the death of Ferdinand I and his sons - Václav Bůžek (Historie - Otázky - Problémy, 2015)
This study considers on the basis of comparative research on written, visual and material sources of interpretations of the symbolic meaning of the means used to represent Ferdinand I and his sons Maximilian II, Charles of Styria, and Ferdinand of Tyrol, during public rituals at their funerals in Vienna, Prague, Graz, and Innsbruck. In methodological terms it rests largely on the Kantorowicz concept of the King’s Two Bodies.